STRATEGI KEPALA SEKOLAH DALAM MENGELOLA MUTU KURIKULUM PENDIDIKAN AGAMA ISLAM - Ahmad Afghor Fahruddin (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2020)
The principal's strategy determines the success in determining the quality of the Islamic religious education curriculum, naming the quality of the Islamic religious education curriculum is like explaining what the principal's strategy concept is, the concept of quality, the concept of the PAI curriculum, and the concept of quality management of the PAI curriculum. So that the principal's efforts to improve the quality of the PAI curriculum are very instrumental, if the principal cannot standardize then the PAI curriculum will not be implemented properly, and must be supported by various parties, the most important thing is the cooperation of Islamic religious education teachers. The principal must carry out his obligations as well as planning, implementing, organizing, supervising, and evaluating. Conducting reviews every year, improving the quality of human resources, and an improved art culture. In planning by setting educational goals , and the necessary documents for the provision of resources, supervision activities, curriculum analysis and evaluation, recordings as evidence of the educational process have taken place. Implementation, according to the vision and mission. Organizing, coordinating and synergizing within the framework of the team in accordance with the management structure in the educational institution. Supervision is monitoring, evaluation, and follow-up. Evaluation of curriculum quality is carried out by the principal to ensure that the activities and results meet the specified requirements, in accordance with the quality goals of educational institutions